Ride on female for “prima nocta” or close attachment in the araneid spider Caerostris sumatrana Strand, 1915 (Araneae: Araneidae) - Omelko, Mikhail M.; Marusik, Yuri M. (Zootaxa, 2023)
A unique type of mate guarding behavior is discovered in the araneid spider Caerostris sumatrana Strand, 1915: the male waits for the female’s maturity while staying tied to the dorsal surface of her abdomen. The species is redescribed in detail. General appearance of the male and its fine structures are illustrated by scanning electron microscopy for the first time. Genital emasculation in the male of this species is reported for the first time.